2015
DOI: 10.1371/journal.pone.0115089
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Equine Groove Model to Induce Metacarpophalangeal Osteoarthritis: A Pilot Study on 6 Horses

Abstract: The aim of this work was to develop an equine metacarpophalangeal joint model that induces osteoarthritis that is not primarily mediated by instability or inflammation. The study involved six Standardbred horses. Standardized cartilage surface damage or “grooves” were created arthroscopically on the distal dorsal aspect of the lateral and medial metacarpal condyles of a randomly chosen limb. The contralateral limb was sham operated. After 2 weeks of stall rest, horses were trotted 30 minutes every other day fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 27 publications
0
35
1
3
Order By: Relevance
“…In an equine metacarpophalangeal groove model, Manninchedda et al 76 showed that synovial fluid levels of C2C, COMP, CTX-I, osteocalcin (OC), and CS-846 were not significantly different between groups. 76 …”
Section: Horsesmentioning
confidence: 99%
“…In an equine metacarpophalangeal groove model, Manninchedda et al 76 showed that synovial fluid levels of C2C, COMP, CTX-I, osteocalcin (OC), and CS-846 were not significantly different between groups. 76 …”
Section: Horsesmentioning
confidence: 99%
“…Animal models, in which hyaline articular cartilage (HAC) was experimentally impacted [14] or joint instability was experimentally induced [5], showed rapid progression of joint damage, at the level of the cartilage and subchondral bone [2, 68]. Surgical management to achieve stabilization of the knee failed to abrogate the development of post-traumatic osteoarthritis (PTOA) [9, 10], indicating that a biochemical disturbance in the HAC of the affected joint is implicated in the accelerated rate of joint degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Considering animal models of PTOA, racehorses sustaining repetitive impact joint injuries, during their athletic career, are likely to develop DJD shortly after the initial inflammatory event affecting the joints [2, 4, 6, 7]. This progression was bound to occur at a much faster rate than in humans [22, 23], although there are currently not enough investigations and consensus about this statement.…”
Section: Introductionmentioning
confidence: 99%
“…e age of horses used ranges from 2 to 6 years. Defects have been created in the femoral trochlea [83], the medial femoral condyle [84], the lateral trochlear ridge [85], and the medial surface of lateral trochlea of the talus [86]. A 10 mm in diameter and 5 mm-10 mm deep defect has often been created to simulate osteochondral defects.…”
Section: 5mentioning
confidence: 99%